2021
DOI: 10.1186/s12910-021-00713-4
|View full text |Cite
|
Sign up to set email alerts
|

The association between perceived hospital ethical climate and self-evaluated care quality for COVID-19 patients: the mediating role of ethical sensitivity among Chinese anti-pandemic nurses

Abstract: Background The COVID-19 pandemic called for a new ethical climate in the designated hospitals and imposed challenges on care quality for anti-pandemic nurses. Less was known about whether hospital ethical climate and nurses’ ethical sensitivity were associated with care quality. This study examined the association between the perceived hospital ethical climate and self-evaluated quality of care for COVID-19 patients among anti-pandemic nurses, and explored the mediating role of ethical sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(49 citation statements)
references
References 42 publications
6
43
0
Order By: Relevance
“…Nevertheless, nurses perceived high perception of the other dimension; efficiency, organizational rules and procedures, personal morality, and laws and professional codes as almost all nurses reported that they have trust and loyalty toward hospital, compliance with the law and professional standards. This is similar to Özden et al 41 and Taraz et al 47 However, Abdeen and Attia 46 and Jiang et al 51 revealed that nurses reported high ethical climate during COVID-19. On the other hand, Constantina et al 52 showed that nurses perceived low ethical work climate.…”
Section: Discussionsupporting
confidence: 85%
“…Nevertheless, nurses perceived high perception of the other dimension; efficiency, organizational rules and procedures, personal morality, and laws and professional codes as almost all nurses reported that they have trust and loyalty toward hospital, compliance with the law and professional standards. This is similar to Özden et al 41 and Taraz et al 47 However, Abdeen and Attia 46 and Jiang et al 51 revealed that nurses reported high ethical climate during COVID-19. On the other hand, Constantina et al 52 showed that nurses perceived low ethical work climate.…”
Section: Discussionsupporting
confidence: 85%
“…This study aimed to investigate the relationship between the ethical work climate of an organization and the intention to leave the service among emergency medical technicians during the COVID-19 pandemic. Based on our findings, the average score of the organization's ethical work climate was at a moderate level, which is consistent with the findings of studies such as Donkers et al ( 19 ) and Jiang et al ( 20 ). Among the dimensions of the ethical work climate of the organization, only the dimension of law received a low score, and the average scores of the other dimensions were at a moderate level.…”
Section: Discussionsupporting
confidence: 92%
“…It is possible that the EMTs did not have enough opportunities to comply with the regulations and were somehow confused, which in turn has harmed the overall score of the work ethics of the organization. Like the ethical work climate score, the EMTs’ average score of the intention to leave the service was at a moderate level, similar to studies by Mirzaei et al ( 10 ) and Zandian et al ( 20 ), both conducted in the same period of time in Iran. Moreover, among the demographic variables, there was a significant relationship between EMTs’ age and employment status, and the ethical work climate and intention to leave the service scores.…”
Section: Discussionsupporting
confidence: 82%
“… 43 Further, the present study is compatible with the literatüre. 42 45 Midwives working in the intensive care unit had higher scores than the midwives working in the delivery room. Since the data were collected during the Covid-19 pandemic, the midwives working here face more moral problems.…”
Section: Discussionmentioning
confidence: 99%